Ocular hemodynamics and activity of autonomic nervous system at different stages of the course of anterior uveitis - N.I. Khramenko (Ukrainian Society of Ophthalmologists, 2015)
Background: Given the complex pathogenetic mechanism of the development of uveitis, it is important to investigate the features of the interaction between the immune, vascular and nervous systems, the level of their activity, and the potential for preventing the development of irreversible morphological changes. Purpose: To investigate the hemodynamic state of the eye and activity of autonomic nervous system in anterior uveitis at different stages of the inflammatory process. Materials and Methods: The study involved 66 anterior uveitis patients. They underwent general clinical examination and ophthalmic rheography involving measurement of pulsatile ocular blood flow (POBF, indicated by RQ, ‰ index), maximum blood flow velocity in the eye (? index, Om/s), and vascular tone (alpha/T percentage index) with Reocom, the computerized rheography apparatus. Results and Discussion: The level of POBF was found to depend on the level of activity of the process, with the Spearman correlation rank rho= 0.26 (P < 0.05). The lowest RQ index values, RQ = (2.54 ± 0.6)‰, were found in steady remission of chronic uveitis, and were statistically significantly lower by 32% (P < 0.05) than those in exacerbation of the disease. Ocular blood flow velocity changes were similar to those of pulsatile ocular blood flow. A direct relationship was revealed between index RQ (‰) and erythrocyte sedimentation rate (ESR, mm/h), an indicator of inflammatory activity (rho = 0.45, P < 0.05). In patients with anterior uveitis complicated by macular edema, the RQ levels and the tone of major ocular vessels during exacerbation episodes were found to be by 54% (P = 0.02) and by 35.5% (P = 0.001), respectively, higher than those in patients with uncomplicated anterior uveitis. In anterior uveitis patients with macular edema, the LF index was by 46% higher (P = 0.02) than in those with uncomplicated anterior uveitis, that is, excessive sympathicotonia was accompanied by retinal damage. Conclusion: We found the ocular hemodynamics features of anterior uveitis depending on the stage of inflammatory process, and the mechanisms of influence of different subsystems of the autonomic nervous system on the hemodynamic state of the eye and complicated course of uveitis.